Sources of fine particulate matter and risk of preterm birth in connecticut, 2000-2006: A longitudinal study - Pereira, Gavin; Bell, M.; Lee, H.; Koutrakis, P.; Belanger, K. (US Department of health Human Sciences National INST of Health Science, 2014)
Background: Previous studies have examined fine particulate matter (= 2.5 µm; PM2.5) and preterm birth, but there is a dearth of longitudinal studies on this topic and a paucity of studies that have investigated specific sources of this exposure. Objectives: Our aim was to assess whether anthropogenic sources are associated with risk of preterm birth, comparing successive pregnancies to the same woman. Methods: Birth certificates were used to select women who had vaginal singleton live births at least twice in Connecticut during 2000-2006 (n = 23,123 women, n = 48,208 births). We procured 4,085 daily samples of PM2.5 on Teflon filters from the Connecticut Department of Environmental Protection for six cities in Connecticut. Filters were analyzed for chemical composition, and Positive Matrix Factorization was used to determine contributions of PM2.5 sources. Risk estimates were calculated with conditional logistic regression, matching pregnancies to the same women. Results: Odds ratios of preterm birth per interquartile range increase in whole pregnancy exposure to dust, motor vehicle emissions, oil combustion, and regional sulfur PM2.5 sources were 1.01 (95% CI: 0.93, 1.09), 1.01 (95% CI: 0.92, 1.10), 1.00 (95% CI: 0.89, 1.12), and 1.09 (95% CI: 0.97, 1.22), respectively. Conclusion: This was the first study of PM2.5 sources and preterm birth, and the first matched analysis, that better addresses individual-level confounding potentially inherent in all past studies. There was insufficient evidence to suggest that sources were statistically significantly associated with preterm birth. However, elevated central estimates and previously observed associations with mass concentration motivate the need for further research. Future studies would benefit from high source exposure settings and longitudinal study designs, such as that adopted in this study.